A PSYCHOANALYTIC APPROACH - WIJAYANTI, RATRI PUTU (2011)
The research is proposed to analyze Bella’s strive for love with psychoanalytic Approach. There are two objectives; the first to analyze Bella’s strive for love in Twilight movie based on psychoanalytic approach, and the second is to analyze Catherine Hardwicke’s Twilight movie based on structural elements of the movie. This study is a descriptive qualitative study, using the movie of Catherine Hardwicke’s Twilight and Twilight’s major character as the object of analysis of the study. There are two kinds of data sources used in this analysis, namely primary data and the secondary. The primary data sources are the play and script of the play itself and the secondary data sources are some books, internet, and articles related to the subject. The technique of the data collection in this research is watching the original movie for several times; reading the movie script; determining the character that will be analyzed; taking notes of important thing both of primary and secondary data sources; classifying and determining the relevant data; notes the material and other resources that related into the movie and the analysis. In analyzing the data, the researcher employs descriptive qualitative analysis. For the last, the researcher makes an analysis of Bella’s id, ego, and superego. The researcher uses the theory of Psychoanalytic by Sigmund Freud because it is relevant to the problem. Based on the analysis, the outcome of this study shows that Bella’s character described as seventeen years old, silence type person, does not like wet and something cold, can not dance, and fall in love with a vampire, Edward. The striving for love toward the main character can be divided into knows that her mother does not happy for Bella lives together with her, knows who Edward is, become the sadistic vampire’s prey, and knows that Edward and her mother ask her to moves from Forks. Bella can strive in order to her still together with Edward.